Pendampingan dan Bimbingan Teknis Penggunaan Media Pembelajaran D’Volleyball Learning Application Bagi Guru PJOK di Kabupaten Ogan Ilir - Destriani, Destriani; Yusfi, Herri; Destriana, Destriana; Agung Nanda, Fitri; Aryanti, Silvi; Richard Victorian, Ahmad; Saputra, Dandi; Mujahidin, Amirul (PELITA NUSA TENGGARA, 2026)
The learning media that was developed in 2022, initially in the form of an application called